Excess burden and the cost of inefficiency in public services provision - Afonso, António (2010)
In this paper we revisit the literature on the economic consequences from inefficiency in public services provision. Following Dupuit (1844) and Pigou (1947) we argue that it is important to take the financing side explicitly into account. The fact that public expenditure financing must rely on distortional taxation implies that both direct and indirect costs are relevant when estimating the economic impacts of inefficiency in public services provision. Using Hicks' compensating variation (following Diamond and McFadden (1974) and Auerbach (1985)) we show that these magnification mechanisms are not only conceptually relevant, they are also important from a quantitative point of view. Specifically, we rely on a range of estimates of public sector efficiency (from Afonso, Schuknecht and Tanzi (2005, 2006)) to illustrate numerically that the relative importance of indirect costs of public sector provision inefficiency, linked to financing through distortional taxation increases with the magnitude of the inefficiency.